General concepts of "Achromatic", "Chromatic", "Primary", "Brick" and "Additional" colors in visual arts (Eurasian Journal of Learning and Academic Teaching, 2023)
This article provides general information about achromatic, chromatic, warm and cold, primary and secondary colors taught in color science, which is considered a branch of fine art, comments on colors, and for brush owners describes a wide range of knowledge and skills related to working with color in the creative process.